DINAMIKA VIRALISASI KASUS HUKUM PERKOSAAN DI MEDIA SOSIAL: Analisis Dampak dan Strategi Terhadap Penegakan Hukum - Arif Sugitanata; Ihda Shofiyatun Nisa’; Siti Aminah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This study explores the dynamics and consequences of the virtualization of legal cases on social media and its impact on law enforcement, such as rape cases. By analyzing both the positive and negative aspects of this viral nature, the research offers an in-depth construction of legal supremacy regarding how social media influences transparency, speed, and public participation in the enforcement of rape laws. A qualitative research methodology is employed, involving an extensive literature review from various sources, including books, scientific journals, and websites discussing rape cases. The research identifies that the virtualization of legal cases like rape allows the public to influence the outcomes of legal processes, marking a shift in the power dynamics between legal institutions and the community. However, this phenomenon also has drawbacks, including public opinion trials often based on biased and incomplete information, which disrupt investigations and tarnish reputations before justice is pretty achieved. Therefore, a balanced strategy is necessary to use social media as a sustainable legal empowerment tool without sacrificing the integrity of justice. The study also faces limitations that could be explored further by future researchers, such as reliance on secondary data and focusing on a specific case, which may not reflect the general dynamics of virtualization. Moreover, based on the research findings, it suggests the development of policies to enhance transparency and accountability and digital literacy programs to educate the public on critically evaluating information from social media regarding cases like rape.